Pengaruh Edukasi Media E-Booklet Terhadap Pola Asuh Pemberian Makanan Dengan Kejadian Stunting Pada Balita - Rajia, Rajia; Indang, Wa Ode; Sitti Zulaeha, Wa Ode (Madu : Jurnal Kesehatan, 2024)
Stunting is a condition of growth and development failure in children caused by chronic malnutrition. Poor maternal parenting patterns in feeding will cause child development to be slow compared to good parenting patterns. One effort to improve knowledge and practice of good parenting patterns is through education using e-booklet media. This study aims to analyze the effect of e-booklet education on maternal parenting patterns with stunting incidents in toddlers. This study used a quasi-experimental design with a pretest-posttest design. The research sample was 60 samples taken using purposive sampling techniques according to the research inclusion criteria. Data were collected using questionnaire instruments and toddler anthropometric measurements. The results of the study showed the characteristics of age (p-value = 0.112), education (p-value = 0.501), occupation (p-value = 0.742), and parenting (p-value = 0.691) where p-value > 0.05 which means there is no significant difference in the incidence of stunting, but the average parenting pattern of mothers of toddlers in the pretest demandigness (37,300) and responsiveness (37,200), while in the posttest demandigness (39,566) and responsiveness (39,350) and the results of statistical analysis obtained parenting patterns demandigness (p-value = 0.010) and responsiveness (p-value = 0.000), this shows a p-value <0.05 which means there is a significant difference before and after providing education through e-booklet media on parenting patterns of mothers of toddlers in providing food.